2016
DOI: 10.1177/0886260515586360
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Sociodemographic Characteristics, Work Conditions, and Level of “Mobbing” of Health Workers in Primary Health Care

Abstract: Mobbing is a type of violence which occurs in workplaces and is classified under the community violence subgroup of interpersonal violence. The aim of this study is to examine health care workers who work in primary health care in the city of Mugla and to determine whether there is a relationship between sociodemographic characteristics, work conditions, and their level of mobbing. A cross-sectional analysis has been conducted in which 130 primary health care workers were selected. Of the 130, 119 health worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 45 publications
3
27
0
2
Order By: Relevance
“…The results of the present study showed that there was no correlation between gender and the victims of workplace harassment since both males and females were exposed to workplace harassment at a similar rate. Similar findings have also been reported by other researchers [43,45,47]. On the other hand, based on the results of other studies, females were shown to have a higher exposure to workplace harassment than males [40].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the present study showed that there was no correlation between gender and the victims of workplace harassment since both males and females were exposed to workplace harassment at a similar rate. Similar findings have also been reported by other researchers [43,45,47]. On the other hand, based on the results of other studies, females were shown to have a higher exposure to workplace harassment than males [40].…”
Section: Discussionsupporting
confidence: 91%
“…The results of our study showed that psychological violence was exercised, in most cases, from females and from people holding a higher hierarchical position such as managers. Results from other surveys also showed that women are more often the perpetrators of psychological violence, [41] as well as people who have leading positions in the organization [8,12,34,[42][43][44]. However, this is not always the case, since other studies have shown males as being the perpetrators of workplace harassment at a higher level than that of females [9,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Picakciefe, Acar, Colak, and Kilic (2015) showed that 31.1% of health workers have experienced mobbing in the last year. Similarly, the results of Gök (2011) showed that among their respondents 32 % were victims of mobbing during the entire working life and 16 % of participants within the last year.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of scientific literature has failed to detect analogous integrated models that would be offered in the development of the culture of management to deal with questions of the prevention of mobbing in social enterprises. Other studies carried out in organisations operating in different areas examine narrower questions, to which the suggestions are oriented as well; for example, to define the responsibilities more precisely (Picakciefe, Acar, Colak, & Kilic, 2015), to shape the staff-oriented culture and to increase awareness of companies of the problems of harassment (Bailien et al, 2011a), to give attention to improving conflict management style is also emphasised (Baillien, Notelaers, De Witte, & Matthiesen, 2011b), and to implement prevention and management programmes (Stagg & Sheridan, 2010). However, in this research, attention is drawn to the fact that persons who work in social enterprises can have special physical needs, and so elimination of mobbing and other negative relationships is impossible without a systematic approach, which is emphasised by the management culture.…”
Section: Conclusion and Discussionmentioning
confidence: 99%